COVID-19, nursing publication and the future of nursing research infection - Salam Banihani (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
Despite the advance in health sciences, the more frequent emerging of infectious diseases in recent decades raise due to environmental changes such as human activity, poor health care system, microbial adaptation, and substantial international movement [1]. This virus has a high mutation ratio with a substantial spread among the population through droplets, airborne, and contact as modes of transmission [2]. Generally, the Coronavirus affected our way of life and specifically the way of carrying out the research.